1997
DOI: 10.1016/s0969-2126(97)00210-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the chemotaxis receptor methyltransferase CheR suggests a conserved structural motif for binding S-adenosylmethionine

Abstract: The CheR structure shares some structural similarities with small molecule DNA and RNA methyltransferases, despite a lack of sequence similarity among them. In particular, there is significant structural preservation of the S-adenosylmethionine-binding clefts; the specific length and conformation of a loop in the alpha/beta domain seems to be required for S-adenosylmethionine binding within these enzymes. Unique structural features of CheR, such as the beta subdomain, are probably necessary for CheR's specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
137
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 52 publications
(67 reference statements)
3
137
0
Order By: Relevance
“…CheR is composed of a small N-terminal domain and a larger C-terminal domain with a seven-stranded modified Rossmann nucleotide-binding fold characteristic of class I methyltransferases (18,19). A small β-subdomain is inserted into the C-terminal domain of CheR.…”
mentioning
confidence: 99%
“…CheR is composed of a small N-terminal domain and a larger C-terminal domain with a seven-stranded modified Rossmann nucleotide-binding fold characteristic of class I methyltransferases (18,19). A small β-subdomain is inserted into the C-terminal domain of CheR.…”
mentioning
confidence: 99%
“…We have addressed this show that the amide moiety of myxothiazol A is hydrolyzed by MelJ resulting in the formation of myxothiazol acid which is subsequently methylated by MelK to the methyl ester ( Figure 3, pathway B). Interestingly, a similar mechanism of methyl ester formation is described for bacterial chemotaxis transmembrane factors in Salmonella typhimurium [25,26]. Theoretically, free melithiazol acid might alternatively be released by the hydrolase from the ACP of MelF and thus MelG might not be required for melithiazol biosynthesis.…”
Section: In Vivo Analysis Of the Final Steps In Melithiazol Biosynthesismentioning
confidence: 74%
“…Early studies on the photochemical cross-linking of purines have shown that substitution/addition reactions can occur either across the 1,6 double bond (64) The AdoMet binding domain of MTases exhibits a comparable three-dimensional folding (27)(28)(29). This structural similarity extends to the tertiary positions of the amino acid side chains interacting with the AdoMet molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the poor overall sequence identity across AdoMet-dependent MTases and varied substrate specificity, these enzymes display a structurally conserved cofactorbinding domain termed the "AdoMet-binding fold" (27)(28)(29). Moreover, a structural conservation of the mode of cofactor binding is observed across most structurally defined members of this superfamily; this has led to the delineation of a set of consensus AdoMet binding interactions (28).…”
mentioning
confidence: 99%